Prediksi Nilai Cryptocurrency Bitcoin menggunakan Algoritme Extreme Learning Machine (ELM) - Rahmat Faizal; Budi Darma Setiawan; Imam Cholisoddin (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Bitcoin is one of cryptocurrency which is popular among people due to decentralized management, well-maintained confidentiality, and easy process. But, this type of cryptocurrency is extremely volatile which makes the owner feel aggrieved. Lots of actions have been taken to overcome this by seeing the statistic movement over and over, Taking actions without considering the future prospect, or make the the asset being untouched until the considered time. Those are inneficient regarding the goal is to get the profit.Therefore, the need of system which can predict the value of Bitcoin accurately and efficiently so it can help decreasing the risk of losing and could give another consideration on trading cryptocurrency Bitcoin. This research has a purpose to obtain the value of cryptocurrency Bitcoin using Extreme Learning Machine (ELM) algorithm. Based on the implementation and analysis conducted using Bitcoin Data from May 1th, 2018 until August 1th, 2018, it can be obtained that the smallest error value using Mean Average Percentage Error (MAPE) is 2,657% with the number of features is 2, the number of hudden neuron is 4, and the percentage of training data is 90%, also the range of with range [-1.8, 1.8].